Aerobic response to thermal stress across ontogeny and habitats in a teleost fish - Eric V. C. Schneider; Zachary C. Zuckerman; Brendan S. Talwar; Steven J. Cooke; Aaron D. Shultz; Cory D. Suski (Journal of Fish Biology, 2023)
Near‐future climate change projections predict an increase in sea surface temperature that is expected to have significant and rapid effects on marine ectotherms, potentially affecting a number of critical life processes. Some habitats also undergo more thermal variability than others, and the inhabitants therefore must be more tolerant to acute periods of extreme temperatures. Mitigation of these outcomes may occur through acclimation, plasticity or adaptation, although the rate and extent of a species' ability to adjust to warmer temperatures is largely unknown, specifically as it pertains to effects on various performance metrics in fishes that inhabit multiple habitats throughout ontogenetic stages. Here, the thermal tolerance and aerobic performance of schoolmaster snapper ( Lutjanus apodus Walbaum, 1792) collected from two different habitats were experimentally assessed under different warming scenarios (temperature treatments = 30, 33, 35, 36°C) to assess vulnerability to an imminently changing thermal habitat. Larger subadult and adult fish collected from a 12 m deep coral reef exhibited a lower critical thermal maximum (CT max ) compared to smaller juvenile fish collected from a 1 m deep mangrove creek. However, the CT max of the creek‐sampled fish was only 2°C above the maximum water temperature measured in the habitat from which they were collected, compared to a CT max that was 8°C higher in the reef‐sampled fish, resulting in a wider thermal safety margin at the reef site. A generalized linear model showed a marginally significant effect of temperature treatment on resting metabolic rate (RMR), but there were no effects of any of the tested factors on maximum metabolic rate or absolute aerobic scope. Post hoc tests revealed that RMR was significantly higher for creek‐collected fish at the 36°C treatment and significantly higher for reef‐collected fish at 35°C. Swimming performance [measured by critical swimming speed] was significantly lower at the highest temperature treatment for creek‐collected fish and trended down with each successive increase in temperature treatment for reef‐collected fish. These results show that metabolic rate and swimming performance responses to thermal challenges are somewhat consistent across collection habitats, and this species may be susceptible to unique types of thermal risk depending on its habitat. We show the importance of intraspecific studies that couple habitat profiles and performance metrics to better understand possible outcomes under thermal stress.

Resist‐accept‐direct (RAD) considerations for climate change adaptation in fisheries: The Wisconsin experience - Zachary S. Feiner; Aaron D. Shultz; Greg G. Sass; Ashley Trudeau; Matthew G. Mitro; Colin J. Dassow; Alexander W. Latzka; Daniel A. Isermann; Bryan M. Maitland; Jared J. Homola; Holly S. Embke; Michael Preul (Fisheries Management and Ecology, 2022)
Decision‐makers in inland fisheries management must balance ecologically and socially palatable objectives for ecosystem services within financial or physical constraints. Climate change has transformed the potential range of ecosystem services available. The Resist‐Accept‐Direct (RAD) framework offers a foundation for responding to climate‐induced ecosystem modification; however, ecosystem trajectories and current practices must be understood to improve future decisions. Using Wisconsin's diverse inland fisheries as a case study, management strategies for recreational and subsistence fisheries in response to climate change were reviewed within the RAD framework. Current strategies largely focus on resist actions, while future strategies may need to shift toward accept or direct actions. A participatory adaptive management framework and co‐production of policies between state and tribal agencies could prioritise lakes for appropriate management action, with the goal of providing a landscape of diverse fishing opportunities. This knowledge co‐production represents a process of social learning requiring substantial investments of funding and time.

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Contemporary and emerging fisheries in The Bahamas—Conservation and management challenges, achievements and future directions - Krista D. Sherman; Aaron D. Shultz; Craig P. Dahlgren; Claire Thomas; Edward Brooks; Annabelle Brooks; Daniel R. Brumbaugh; Lester Gittens; Karen J. Murchie (Fisheries Management and Ecology, 2018)
The harvest of marine resources has long‐standing cultural and economic importance to The Bahamas and other small island developing states. Tourists and residents place a demand on local marine resources, particularly Caribbean spiny lobster , Panulirus argus (Latreille), queen conch, Lobatus gigas (Linnaeus) and Nassau grouper, Epinephelus striatus (Bloch), and many fishery products are also sold on the global market. Illegal, unreported and unregulated fishing coupled with inadequate regulations and enforcement are the main factors contributing to the decline of Bahamian fisheries along with other anthropogenic impacts. This article reviews the status of fisheries management in The Bahamas using economically and ecologically important species as case studies to highlight conservation successes, knowledge gaps and deficiencies in existing management approaches. The review concludes with an examination of how emerging fisheries and improved conservation management strategies have the potential to improve economic and food security throughout the archipelago.

Potential consequences of angling on nest-site fidelity in largemouth bass - William M. Twardek; Aaron D. Shultz; Julie E. Claussen; Steven J. Cooke; Jeffrey A. Stein; Jeffrey B. Koppelman; Frank J. S. Phelan; David P. Philipp (Environmental Biology of Fishes, 2017)

Thermal tolerance of nearshore fishes across seasons: implications for coastal fish communities in a changing climate - Aaron D. Shultz; Zachary C. Zuckerman; Cory D. Suski (Marine Biology, 2016)

Impacts of sun protection on feeding behavior and mucus removal of bonefish, Albula vulpes - Kelly D. Hannan; Zachary C. Zuckerman; Christopher R. Haak; Aaron D. Shultz (Environmental Biology of Fishes, 2015)

Swimming energetics and thermal ecology of adult bonefish (Albula vulpes): a combined laboratory and field study in Eleuthera, The Bahamas - Liane B. Nowell; Jacob W. Brownscombe; Lee F. G. Gutowsky; Karen J. Murchie; Cory D. Suski; Andy J. Danylchuk; Aaron Shultz; Steven J. Cooke (Environmental Biology of Fishes, 2015)

Defining adult bonefish (Albula vulpes) movement corridors around Grand Bahama in the Bahamian Archipelago - Karen J. Murchie; Aaron D. Shultz; Jeffrey A. Stein; Steven J. Cooke; Justin Lewis; Jason Franklin; Greg Vincent; Edward J. Brooks; Julie E. Claussen; David P. Philipp (Environmental Biology of Fishes, 2015)

Aggregations and offshore movements as indicators of spawning activity of bonefish (Albula vulpes) in The Bahamas - Andy J. Danylchuk; Steven J. Cooke; Tony L. Goldberg; Cory D. Suski; Karen J. Murchie; Sascha E. Danylchuk; Aaron D. Shultz; Christopher R. Haak; Edd J. Brooks; Annabelle Oronti; Jeff B. Koppelman; David P. Philipp (Marine Biology, 2011)